Urban public transport in informal settlements: Experiences from Kisumu City, Kenya - Onyango, George Mark (Bulletin of Geography. Socio-economic Series, 2018)
Kisumu has had a massive growth of informal settlements forming a belt around the urban core. These settlements house more than half of the city's population. Because of the unplanned nature of these areas there has been very poor road infrastructure development, with narrow, unpaved roads constituting the road infrastructure. This situation has limited the opportunities for regular urban transport minibuses providing transport for the majority of the urban poor who live in these settlements. The coping mechanism and the development of alternative coping strategies are explored and assessed to see how effective they are in providing public transport for this majority of unserviced urban population.